Analysis of the Implementation of Income Tax Accounting Article 21 at The Food Security Service Of Deli Serdang Regency - Hutahaean, Sondang Lastiur; Renny Maisyarah (CERED Indonesia Institute, 2024)
This study aims to analyze the implementation of Income Tax (PPh) Article 21 at the Food Security Service of Deli Serdang Regency. PPh Article 21 is a tax imposed on income in the form of salaries, wages, honorariums, and other payments related to work or position. Compliance in the implementation of PPh Article 21 is very important to support state revenues while reflecting transparent and accountable financial governance. This research method uses a qualitative descriptive approach with primary data obtained through interviews with financial management officials at the Food Security Service of Deli Serdang Regency and secondary data in the form of tax reporting documents. The analysis was carried out to evaluate the process of calculating, deducting, depositing, and reporting PPh Article 21 in accordance with applicable provisions. The results of the study indicate that the Food Security Service of Deli Serdang Regency has carried out its PPh Article 21 tax obligations quite well. However, there are several obstacles, such as the lack of understanding of some employees regarding tax provisions, delays in tax payments, and the less than optimal use of information technology in the reporting process. The implementation of Article 21 Income Tax in the Food Security Service of Deli Serdang Regency requires improvement to increase compliance and efficiency. It is recommended that the service conduct routine training related to taxation for employees, increase supervision of the tax payment and reporting process, and utilize information technology to support more effective and efficient tax management.